2003
DOI: 10.1080/09546630310009491
|View full text |Cite
|
Sign up to set email alerts
|

An open‐label pilot study to evaluate the safety and efficacy of topically applied tacrolimus ointment for the treatment of hand and/or foot eczema

Abstract: Tacrolimus ointment 0.1% is a promising corticosteroid alternative for hand/foot eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…In Table 1 the search terms for our systematic search in both databases are given separately and the corresponding results are shown. Table 2 5,10,15–81 gives an overview of all the studies using scoring systems for assessing hand eczema severity. Table 2 includes a detailed comparison of published semiquantitative hand scores in both databases including the date of publication of the manuscript, the sample size and characterization of the study population, the score used, the potential combination with subjective complaints and the maximum score value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 1 the search terms for our systematic search in both databases are given separately and the corresponding results are shown. Table 2 5,10,15–81 gives an overview of all the studies using scoring systems for assessing hand eczema severity. Table 2 includes a detailed comparison of published semiquantitative hand scores in both databases including the date of publication of the manuscript, the sample size and characterization of the study population, the score used, the potential combination with subjective complaints and the maximum score value.…”
Section: Resultsmentioning
confidence: 99%
“…These scores were first and foremost used for assessing the skin condition of participants with distinct hand eczema 5,10,15–19,21–25,27–31,33,35–38,41–43,45,47,49–60,62–65,67–70,74–78,80 except two studies that included only healthy volunteers 40,48 . In 16 trials the participants were exposed to ‘hazardous substances at workplace’ potentially harmful to their skin 18–20,23,26,32,34,38,45–47,57,65,66,71,73 .…”
Section: Resultsmentioning
confidence: 99%
“…At the end of the study, 28% of patients treated with pimecrolimus versus 18% using vehicle were clinically clear or almost clear of chronic hand eczema -it was ob- 47 served that lesions of the dorsum of the hands had a better response than palmar lesions. In an open study, Thelmo et al showed that tacrolimus 0.1% ointment, used three times daily, improved lesions of hand and foot eczema [22] . The systemic absorption of topical pimecrolimus when used under occlusion to treat hand eczema was shown to be minimal and similar to that observed without occlusion in patients with atopic eczema [13,21] .…”
Section: Chronic Hand Dermatitismentioning
confidence: 99%
“…Several clinical studies have evaluated the efficacy and tolerability of TCIs in the treatment of chronic hand dermatitis [20][21][22] , and some benefits have been noted following observational use [23] . In a double-blind controlled study randomizing 294 patients to pimecrolimus or vehicle, Belsito et al have shown that topical pimecrolimus used twice daily, with the evening application followed by 6-hour occlusion with vinyl gloves, reduced the clinical signs of cutaneous inflammation [20] .…”
Section: Chronic Hand Dermatitismentioning
confidence: 99%
“…Their anti-inflammatory potency has been approximated to that of lower mid-strength corticosteroids, such as 0.1 % hydrocortisone butyrate or 0.1 % betamethasone-17-valerate [48,49]. There are several studies in chronic hand eczema [48,50] (reviewed in [51]) where TCIs showed good therapeutic effects worthy of further study in large RCTs. As TCIs may not penetrate well through hyperkeratosis, in some of the studies they were applied under occlusion; for example, twice daily with overnight occlusion [52].…”
Section: Topical Calcineurin Inhibitors (Tcis)mentioning
confidence: 98%